SIFAT PAPAN WOL KAYU DARI 8 JENIS KAYU MALUKU UTARA - I M Sulastiningsih; Paribotro Sutigno; M l Iskandar (Jurnal Penelitian Hasil Hutan, 1995)
The result of  laboratory  test of wood-wool board properties  manufactured from 8 individual wood species  obtained from  North Maluku  are  reported  in this paper.   The  tests  comprising board density,  moisture  content,   thickness  reduction  due  to  compression,   and bending  strength.The study  reveals that  the  average yield  of wood-wool  is  492. 75 kg/m3  of log  input.   The wood-wool  of  Parinari   corymbosa,   Shorea    koordersii,    Hopea   sp.   and  Horsfieldia        sylvestris  must  be  soaked   in  cold  water  for 24 hours prior  to  wood-wool board manufacture,      while the otherfour  species  do not  require   the soaking.  The physical  and mechanical  properties   of wood- wool board from  seven  wood species  mineralized   with Ca CJ 2  are in comformity with  the DIN 1 101   standard.    Only six  wood species,   however,    mineralized    with Ca(OH)2 suspension   meet  the  standard  requirement.     The  identical  commercial   name of wood not  necessarily  produce  a comparable  quality  board.   Apart  from  the  species,   growth  and  environmental   factors   are believed  to contributing  to board properties.